National Defense as an Instrument for Developing the Nationalist Mentality of Indonesian Navy Soldiers - Harun Arrasyid; Abdul Hamid; Zamakhsyari Abdul Majid (Ikatan Sarjana Komunikasi Indonesia, 2025)
This study examines the declining spirit of nationalism among Indonesian Navy (TNI AL) personnel in the context of globalization, which has gradually eroded national values. The purpose of this research is to analyze the role of National Defense (patriotic religious advocacy) as an instrument for fostering soldiers’ nationalist mentality. Using a library research method, data were collected from scholarly literature, books, journals, and relevant documents discussing da’wah, national defense, and nationalism within the military context. The findings indicate that da’wah, when framed within the concept of national defense, can effectively internalize nationalist values through an integrated religious and ideological approach. This study contributes theoretically to the development of value internalization studies within military institutions and emphasizes the importance of integrating da’wah programs into soldiers’ mental and character development systems. The study concludes that National Defense is not merely a spiritual activity but also a strategic effort to shape character and ideological loyalty among military personnel toward the nation and the state.